2019
DOI: 10.1016/j.semradonc.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NAD+ Metabolism to Enhance Radiation Therapy Responses

Abstract: NAD+ metabolism is integrally connected with the mechanisms of action of radiation therapy and is altered in many radiation-resistant tumors. This makes NAD+ metabolism an ideal target for therapies that increase radiation sensitivity and improve patient outcomes. This review provides an overview of NAD+ metabolism in the context of the cellular response to ionizing radiation, as well as current therapies that target NAD+ metabolism to enhance radiation therapy responses. Additionally, we summarize state-of-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…In our previously-developed FBA models of radiation-sensitive and radiation-resistant head and neck squamous cell carcinoma (HNSCC) cell lines, we accurately identified oxidoreductase genes that differentially impacted response to treatment with the NADPH-dependent redox-cycling chemotherapeutic β -lapachone between radiationsensitive and -resistant cells . Additionally, our models suggested that radiation-resistant cancer cells re-route NADH-generating metabolic fluxes through NAD salvage and purine salvage pathways involving NAMPT, an enzyme whose activity has previously been associated with radiation resistance and poor survival in cancer patients (Gujar et al, 2016;Lewis et al, 2019). Here, we extend this approach by developing an automated bioinformatics pipeline for integrating multi-omics information from The Cancer Genome Atlas (TCGA) and publically-available repositories into personalized genome-scale FBA models of 915 patient tumors across multiple cancer types.…”
Section: Introductionmentioning
confidence: 84%
“…In our previously-developed FBA models of radiation-sensitive and radiation-resistant head and neck squamous cell carcinoma (HNSCC) cell lines, we accurately identified oxidoreductase genes that differentially impacted response to treatment with the NADPH-dependent redox-cycling chemotherapeutic β -lapachone between radiationsensitive and -resistant cells . Additionally, our models suggested that radiation-resistant cancer cells re-route NADH-generating metabolic fluxes through NAD salvage and purine salvage pathways involving NAMPT, an enzyme whose activity has previously been associated with radiation resistance and poor survival in cancer patients (Gujar et al, 2016;Lewis et al, 2019). Here, we extend this approach by developing an automated bioinformatics pipeline for integrating multi-omics information from The Cancer Genome Atlas (TCGA) and publically-available repositories into personalized genome-scale FBA models of 915 patient tumors across multiple cancer types.…”
Section: Introductionmentioning
confidence: 84%
“…However, despite these promising results, the translation to clinic has been challenging [e.g., ARQ761 phase I/II clinical trials (Gerber et al, 2018)] limited in part by the lack of knowledge of the molecular factors driving the efficacy of βlap or ARQ761. As the chemotherapeutic activity of β-lap is intrinsically linked to the availability of NAD(P)H, and our prior dynamic flux balance analysis identified mitochondrial MTHFD2 as a key driver of NAD(P)H in HNSCC, including the SCC-61/rSCC-61 cells (20,21), we sought to investigate here the contribution of MTHFD2 to the efficacy of response to β-lap when used alone or combined with ionizing radiation. The focus on MTHFD2 was also driven by the clinical precedent of folate inhibitors for treatment of HNSCC, and key publications showing increased MTHFD2 expression in rapidly proliferating solid tumors compared to normal tissue (29), MTHFD2-mediated folate metabolism playing a pivotal role in the progression and metastasis of several cancer types (30)(31)(32) with evidence that this might occur independent of its enzymatic activity (33), MTHFD2 function in purine and pyrimidine biosynthesis, critical metabolites for DNA synthesis and DNA damage repair (34), and evidence of additional nuclear localization of MTHFD2 at DNA synthesis sites (33).…”
Section: Discussionmentioning
confidence: 99%
“…The HNSCC radiation sensitive SCC-61, genetically matched radiation resistant rSCC-61 cells (17)(18)(19)(20)(21), MTHFD2 knockdown rSCC-61 cells (MTHFD2 KD rSCC-61), and the respective scramble shRNA control rSCC-61 cells (scRNA rSCC-61) were cultured in DMEM/F12 media containing 10% FBS and 1% penicillin/streptomycin at 37 • C using a 5% CO 2 incubator. The cell culture media was replaced every other day and before lysis when the cells reached 80-90% confluency.…”
Section: Hnscc Cells and Cell Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described canonical pathway produces Ado through the metabolism of ATP toward AMP through the action of CD39. Among the extracellular nucleotides that can highly increase and become catabolized under pathologic conditions is also the extracellular nicotinamide adenine dinucleotide (NAD + ) in addition to ATP (51,52). In this non-canonical pathway, extracellular NAD + is metabolized into ADP ribose (ADPR) via the cyclic ADPR hydrolase (CD38).…”
mentioning
confidence: 99%